STRATEGI BERTAHAN HIDUP MASYARAKAT DI PEMUKIMAN KUMUH - Nur Azizah Novianti Yulis; Jamaluddin Hos; Sarmadan Sarmadan (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this study is to (1) describe the community survival strategies in slums. (2) describes the factors of the formation of slum areas in Andounohu Village, Poasia District, Kendari City. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The results showed that people who live in slums have several survival strategies, namely active strategy, passive strategy and network strategy. The active strategy is in the form of efforts to extend working hours, involve family members (women and children) in matters of livelihood, as well as diversifying work. Passive strategy in the form of an effort to make savings in aspects of consumption and substitution of staple foods. Meanwhile, the network strategy is carried out by building good relations with fellow citizens, fellow families, and relationships with parties related to their work.The factors causing the emergence of slums in Anduonohu Urban Village are urbanization in the sense that the region's growth and development become an inseparable part of Kendari City, the difficulty of finding decent jobs for some city residents, and the difficulty of finding decent and affordable housing.